PERUBAHAN LUAS TUTUPAN LAHAN PADA AREAL HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON - Merlin Renny Sitanala; Yulianus Dominggus Komul (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The purpose of this research was to determine changes in forest cover of Mount Sirimau Protected Forest in Ambon City which have been analyzed since 1990, 2000, 2006, 2011 and 2015. This research was conducted using analytical methods where satellite imagery of 5 different years in 1990, 2000 and 2006 recording years, 2011 and 2015 were interpreted digitally through supervised classification. After the interpretation, the mapping was carried out using ArGIS to analyze changes in forest cover. It is supported by the data from the Forest Monitoring Center of Ambon Area IX that had been obtained using ArGIS into primary data. The data were analyzed by using the digital analysis method or the maximum opportunity method. The results showed changes in land cover in 2000, 2006 and 2011 from areas of forest become agricultural land and in 2015 the area of agricultural land was changed into settlements areas. The augmentation of non-forest areas (Settlements) along the Toisapu hamlet and Soya villages up to 2015 for residential areas has reached 16,997 Ha with an average annual increase of 70.59 km2.